Pelatihan Menggunakan Media Bola Terrhadap Kecepatan Reaksi Penjaga Gawang Olahraga Hoki - Ariq Naufal; Nina Sutresna; Ucup Yusup (Fakultas Pendidikan Olahraga dan Kesehatan, Universitas Pendidikan Indonesia, 2021)
The aim of this study was to determine the effect of training methods on the speed reaction of hockey's goalkeeper. According to the movements, a hockey's goalkeeper athlete must have good and precise abilities to withstand shots from opposing players, of course, with speed reaction. This method of this study is using experimental method. This research was conducted at UKM Hoki UPI Bandung involving 7 people using saturated sample sampling technique. The research design was used the pre-test post-test control group. The instrument was used